Recent Advances in Construction of C(sp2)–O Bonds via Aryne Participated Multicomponent Coupling Reactions - Zhang, Ruirui; Peng, Xia; Tan, Jiajing (Synthesis, 2022)
Aryne chemistry is a powerful synthetic technique that forms new bonds to aromatic rings. The recent resurgence of aryne-based multicomponent coupling strategies has led to an influx of methodologies for the mild synthesis of arene derivatives. In particular, these innovative discoveries broaden and streamline approaches toward phenol ether motifs, which are a prevalent structural component across a broad range of chemistry related research fields. Herein, this review aims to provide a comprehensive overview of the recent progress in the construction of C(sp2)–O bonds via aryne-induced multicomponent reactions. Special attention has been paid to reaction design and mechanistic pathways.1 Introduction2 Insertion-Based MCRs3 Nucleophilic-Addition-Based MCRs4 Cycloaddition-Based MCRs5 Summary
Keywords: C(sp2)–O bonds; arynes; multicomponent coupling reaction; phenyl ether derivatives; insertion; nucleophilic addition; cycloaddition